Village of the small houses : a memoir of sorts - Ferguson, Ian, 1959- (Vancouver ; Berkley, CA : Dougals & McIntyre, 2004)
In 1959, just one step ahead of the law, Ian Ferguson's parents left the sophisticated big-city life of Edmonton for Fort Vermilion -- once a fur-trapping frontier town, now a remote aboriginal settlement in northernmost Alberta. There, Ian and his six brothers and sisters grew up without indoor plumbing, electricity, central heating, or even a radio. Beginning with the dramatic events surrounding his birth (including a paddlewheel ferry heading for destruction, a legendary rowboat trip, and a life-and-death race against time), the richly recalled events of Ferguson's life and a vivid array of
Keywords: Ferguson, Ian, 1959- -- Childhood and youth; Ferguson, Ian, 1959- -- Homes and haunts -- Alberta -- Fort Vermilion; Dramatists, Canadian -- 20th century -- Biography; Humorists, Canadian -- 20th century -- Biography; Family -- Alberta -- Fort Vermilion; Fort Vermilion (Alta.) -- Social life and customs; Fort Vermilion (Alta.) -- Intellectual life; Fort Vermilion (Alta.) -- Biography